Rabson-Mendenhall syndrome: A rare case with severe insulin resistance - Hossain, Md Ashraful; Chowdhury, Prodipta; Banu, Hurjahan; Sultana, Nusrat; Jahan, Sharmin; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A rare hereditary cause of insulin resistance, Rabson-Mendenhall syndrome (RMS) is manifested by extreme insulin resistance caused by mutations in the insulin receptor (INSR) gene. The characteristics of RMS are retarded growth, dysmorphisms, hirsutism, enlarged genitalia, acanthosis nigricans, dysplastic dentition, hyperglycemia, elevated insulin level, and hyperplasia of the pineal gland. RMS patients usually present in childhood, and most affected patients usually survive till the second decade of life. We are presenting here a unique case of a 10-year-old girl with very high blood sugar and crowding of teeth. She developed classical symptoms of diabetes for the last three years. On examination, she had syndromic coarse facies, prognathism, gingival hyperplasia, larger lower lip, hyperdontia, hyperpigmented skin, hypertrichosis, severe acanthosis nigricans & dystrophic nails. Biochemical investigations revealed insulin resistance by high fasting insulin, and high normal C-peptide with very high Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). She was treated with insulin with insulin sensitizer-Metformin & Pioglitazone, but her blood glucose was still poorly controlled. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2025;4(2): 80-84